GAMBARAN KUALITAS TIDUR PADA PENDERITA DIABETES MELITUS TIPE-2 DI WILAYAH KERJA PUSKESMAS NGESREP - Tri Damayanti Simanjutak; Lintang Dian Saraswati; Muflihatul Muniroh (Jurnal Kesehatan Masyarakat (Undip), 2018)
Diabetes Mellitus type-2 is a condition when hyperinsulinemia happened but insulin could not bring glucose entering the tissues due to insulin resistance. Clinical symptoms experienced by patients with type-2 diabetes at night can reduce sleep quality. Puskesmas Ngesrep is a health center with the highest proportion of diabetes mellitus type 2 cases compared to other community health centers in Semarang city with percentage around 52.15%. This study aims to describe the quality of sleep in people with diabetes mellitus type 2 in the working area of Puskesmas Ngesrep. The Study design used is cross-sectional with 80 randomly selected samples which is assisted by sample frame listing. The result shows around 56,2% of people with diabetes mellitus type-2 have a bad sleep quality. People with age ≥ 60 years, work in shifts, smokers, and with BMI ≥ 30 Kg/m2, has a worse sleep quality. The people which use lights and cotton filled mattress even has worse sleep quality. Uncontrollable blood sugar level and high level of stress has stronger tendency to have bad quality of sleep. From this study, we can conclude that the sleep quality of people with type-2 diabetes in working area of Puskesmas Ngesrep is bad.